Determinants of sperm competition and the role of cryptic female choice in the broadcast spawning Atlantic cod (Gadus morhua) - Mayer, I; Skjæraasen, J E; Meager, J J; Rudolfsen, G; Karlsen, Ø; Moberg, O; Staby, A; Kleven, O (WFC2008, 2008)
No abstract available.